URBAN REGENERATION OF LARGE HOUSING ESTATES THROUGH THE HQE²R APPROACH – CASE OF BAB EZZOUAR (ALGIERS) - Zakaria Zouggari; Mohamed Cherif Adad (International Journal of Innovative Technologies in Social Science, 2024)
This article aims to adapt HQE²R approach to the Algerian “large housing estates”, through urban regeneration as a catch-up project. These neighborhoods constitute today a large stock of housing, mostly in decay, which deserves to be renewed. Nevertheless, they remain desirable neighborhoods due to their strategic urban location. The methodology consists of establishing a shared diagnosis model of sustainable development called HQDIL for detailed description of ZHUN Soummam according to urban actors, then an SD indicators assessment model called INDI as a decision support tool for the benefit of local authorities and their partners. In our study, we opted for INDI-2012 repository as a new operational tool which makes it possible to produce sustainability profiles through 127 composite indicators and 234 secondary indicators, first of all for an initial diagnosis, then by drawing up a potential scenario which describes the contribution of the urban regeneration project to improving the quality of life. Perceived visually, the neighborhood’s critical state with regard to the SD objectives was confirmed following the results of the assessment by themes, especially the indicators dealing with the quality of life of the inhabitants. The potential scenario for the urban regeneration project showed a very satisfying sustainability profile, if an action plan were to be implemented. The scenario showed a significant improvement in the neighborhood’s level of sustainability of 47% compared to the initial situation. This study promises to lead to a sustainable transformation of large housing estates in Bab Ezzouar thanks to shared challenges and proactive policies.